PENGEMBANGAN KOMPETENSI 4C DAN KETERAMPILAN PROSES SAINS MELALUI PEMBELAJARAN BERBASIS CATUR PRAMANA - I Komang Wisnu Budi Wijaya (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The era of 4.0 industrial revolution requires each individual to have a critical thinking competence, creative thinking, communication and collaboration. These four competencies are known as 4C competencies. In addition, the mastery of science is absolutely necessary because science is the foundation to become a developed country. The mastery of science will be easier to do if every student has a science process skill. The development of 4C competency and science process skill can be done by Catur Pramana based learning. Catur Pramana is four ways to obtain knowledge, namely Sabda Pramana (listening), Praktyasa Pramana (observing), Anumana Pramana (reasoning) and Upamana Pramana (comparing). Each learning activity on every aspect of Catur Pramana encourages student to develop 4C competency and science process skill.